Analisis Penetapan COGM (Cost Of Goods Manufactured) Dengan ABC (Activity Based Costing) Sebagai Metode Pengukuran Harga Jual - Riski Dwi Sahputra; Zulia Hanum (Owner : Riset dan Jurnal Akuntansi, 2023)
The determination of COGM or the cost of production in a company is very important for making decisions on the selling price of a product. Therefore, the determination of methods that produce appropriate and accurate sources of data and information becomes a consideration in business continuity in the future. The ABC (Activity Based Costing) method is one method that is well known for its accuracy compared to traditional/conventional methods. The object of this research is the ITS Back To Nature Business, which is a business engaged in manufacturing by producing marker ink with three color variants, namely black, blue, and red. This business still applies the traditional system in determining COGM or the cost of production. This study aims to determine the accuracy of the two methods of determining COGM by comparing the traditional/conventional method and the ABC (Activity Based Costing) method in measuring the selling price later. This research is classified as a part of qualitative research that adheres to a descriptive approach by providing a systematic description of COGM (Cost Of Goods Manufactured) or the cost of production through the ABC method. Observations, interviews, and documentation are techniques or methods of collecting data in this study. In the findings of this study, the results obtained where the ABC method applied showed a lower cost of goods compared to the traditional/conventional method with a difference of IDR 726 for black ink products, IDR 646 for blue ink, and IDR 1,035 for red ink. This, of course, greatly affects the company's price competitiveness in the market.